Resource-Saving Technologies of Railway Transportation of Grain Freights for Export - Kozachenko, Dmitrii N.; Vernigora, Roman V.; Kuznetsov, Valeriy; Lohvinova, Nataliia A.; Rustamov, Rustam S.; Papahov, Aleksandr Yu. (Politechnika Warszawska; Instytut Transportu, 2018)
ENG: The research objective is to increase the efficiency of export railway transportation of grain freights in Ukraine by the introduction of consignor routing, a concentration of loading of grain on junction elevators and the organization of the movement of grain routes according to the schedule. According to the researchers in USA and EU, one of the effective directions for decreasing the expenses in a logistic chain of grain delivery to ports is consignor routing of railway transportation. Consignor routing of transportations of grain freights provides a concentration of their loading at junctions. The choice of junctions is proposed to be carried out on the basis of methods of the cluster analysis. For formation of regions for a concentration of grain loading the theory of sets and multicriteria optimization are used. As a result, on the basis of the modified simplex method are chosen 24 regions of possible concentration of grain loading that cover 70 stations on Ukrainian railways providing 7,5 million t consignor routing for grain in a year with minimal additional expenses. The assessment of the efficiency of railway transportation routing of grain freights is calculated with use of the developed simulation model. Researches showed that application of consignor routing allows to reduce a turn-round cycle for grain wagon in a logistic chain of deliveries up to 27%, and application of the schedule for consignor routes allows to reduce a turn-round cycle up to 62%, in comparison with transportation by car loading. Thus, as showed the calculations executed for one of the directions of grain transportation for export, the necessary operation park of grain-carrier wagons is reduced twice, thereby allowing to cut logistic expenses on a delivery of the Ukrainian grain through seaports to the world markets.
D. Kozachenko: ORCID 0000-0003-2611-1350; R. Vernigora: ORCID 0000-0001-7618-4617; V. Kuznetsov: ORCID 0000-0003-4165-1056; N. Lohvinova: ORCID 0000-0002-9350-881X; R. Rustamov: ORCID 0000-0002-5860-1840; A. Papahov: ORCID 0000-0003-2357-8158
Keywords: grain export; elevators; rail transportation; consignor routing; concentration of loading; cluster analysis; simulation of railway transport network; КУЕР; КТВ; КІСЕ